2020
DOI: 10.1007/s12630-020-01792-4
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of topical agents for prevention of postoperative sore throat after single lumen tracheal intubation: a Bayesian network meta-analysis

Abstract: Background The optimal choice of prophylactic drugs to decrease postoperative sore throat is unclear. The objective of this network meta-analysis (NMA) was to compare and rank 11 topical agents used to prevent postoperative sore throat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 83 publications
1
7
0
1
Order By: Relevance
“…In a randomised controlled trial, dexamethasone, with or without lidocaine, was effective in reducing the incidence of POST in patients requiring prolonged tracheal intubation 4. Singh et al 5 also found that corticosteroids were among the three topical agents most closely associated with reduction of POST. In our study, the lack of dexamethasone use (OR=5.71) was shown to be a significant risk factor for POST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomised controlled trial, dexamethasone, with or without lidocaine, was effective in reducing the incidence of POST in patients requiring prolonged tracheal intubation 4. Singh et al 5 also found that corticosteroids were among the three topical agents most closely associated with reduction of POST. In our study, the lack of dexamethasone use (OR=5.71) was shown to be a significant risk factor for POST.…”
Section: Discussionmentioning
confidence: 99%
“…Intubation lasting longer than 90 min yielded a higher likelihood (OR=1.27) of POST 4. Various non-pharmacological measures (supraglottic ventilation devices, smaller tracheal tubes, limited cuff pressure and good muscle relaxation) and pharmacological measures (lidocaine, dexamethasone and non-steroidal anti-inflammatory drugs) have been used to prevent or reduce the incidence of this complication 5…”
Section: Introductionmentioning
confidence: 99%
“…We chose the Bayesian inferential framework because it allows external information to be included and can capture and propagate uncertainty. In addition, it will not be biased by small sample size, while the frequentist inference often becomes biased when the sample size decreases ( 29 , 30 ). The OpenBUGS 3.2.3 (members of OpenBUGS Project Management Group, see www.openbugs.net ) and GeMTC 0.14.3 (Generate Mixed Treatment Comparisons, see http://drugis.org/software/addis1/gemtc ) were used for the analysis of time-to-event data (PFS and OS) and the analysis of binary variables (ORR and grade ≥3 AEs), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…35 Singh et al conducted a meta-analysis of 42 trials comparing eight treatment regimens and found that inhaled corticosteroid therapy was the probably the best treatment regimen to reduce the early development of sore throat (4-6 hours from extubation). 36…”
Section: Steroid Therapymentioning
confidence: 99%